Association between UGT1A1 Polymorphism and Risk of Laryngeal Squamous Cell Carcinoma - Huangfu, Hui (Int J Environ Res Public Health, 2016)
Laryngeal cancer is one of the largest subgroups of head and neck cancers. In addition to smoking and alcohol consumption, genetic polymorphisms are also risk factors for the development of laryngeal cancer. However, the exact relation between genetic variants and pathogenesis of laryngeal cancer has remained elusive. The aim of this study was to examine UGT1A1*6 (rs4148323 A/G) polymorphisms in 103 patients with laryngeal cancer and 220 controls using the high resolution melting curve (HRM) technique and to explore the association between UGT1A1*6 (rs4148323 A/G) polymorphisms and laryngeal cancer. The results showed an association between the rs4148323 G allele and increased risk of laryngeal cancer. While there was no statistically significant difference between rs4148323 genotype frequencies and different histological grades or different clinical stages of laryngeal cancer, stratification analysis indicated smoking or alcohol consumption and rs4148323 G allele combined to increase the risk of laryngeal cancer. In conclusion, the rs4148323 G allele is associated with the high UGT1A1 enzyme activity, and might increase the risk of laryngeal cancer. Furthermore, smoking or alcohol consumption and the rs4148323 G allele act synergistically to increase the risk of laryngeal cancer.